RANCANG BANGUN APLIKASI GAME DENGAN TEMA BUILDING ON FIRE BERBASIS VIRTUAL REALITY - Dian Gustina; Muhammad Abi Maulana (Fakultas Ilmu Komputer dan Desain - Unsurya, 2020)
Technology is one part that can not be separated from human life. Various fields in human life have been greatly aided by the existence of technology, especially computer technology. Virtual Reality (VR) is a new way to explore the virtual world. With virtual reality, penguuna seems to be entering a new environment in a virtual world. The vastness of the virtual world can provide many opportunities to produce a variety of fun entertainment games.